2015
DOI: 10.11648/j.ajee.20150304.11
|View full text |Cite
|
Sign up to set email alerts
|

Boiler Parametric Study of Thermal Power Plant to Opproach to Low Irreversibility

Abstract: Abstract:In this work, in order to reach to low irreversibilities, the energy and exergy have been analyzed in the boiler system of Tabriz power plant. First, it has been done to decrease the irreversibility of system. Second, flow and efficiencies of energy and exergy of the mentioned system have been studied. In the boiler, the energy efficiencies based on lower and higher heating value of fuel are 91.54% and 86.17% respectively. In other hand, the exergy efficiency is 43.98%. Comparing with Rosen and et al.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…P. S. Hada and I. H. Shah [10] in a first law and second law analysis of a lignite fired boiler used in a 30MW thermal power plant found the two efficiencies as 85.52% and 33.73%. S. Arefdehgani and O. K. Sadaghiyani [11] in a boiler parametric study of a gas fired steam power plant found the boiler energy efficiency as 91.54% and 86.17% based on lower and higher heating values respectively which were in logical agreement with experimental data. They studied the effect of several measures and concluded that by decreasing excess air fraction from 0.4 to 0.15 energy and exergy efficiency of the plant increases by 0.497% and 0.46% respectively.…”
Section: Introductionsupporting
confidence: 66%
See 1 more Smart Citation
“…P. S. Hada and I. H. Shah [10] in a first law and second law analysis of a lignite fired boiler used in a 30MW thermal power plant found the two efficiencies as 85.52% and 33.73%. S. Arefdehgani and O. K. Sadaghiyani [11] in a boiler parametric study of a gas fired steam power plant found the boiler energy efficiency as 91.54% and 86.17% based on lower and higher heating values respectively which were in logical agreement with experimental data. They studied the effect of several measures and concluded that by decreasing excess air fraction from 0.4 to 0.15 energy and exergy efficiency of the plant increases by 0.497% and 0.46% respectively.…”
Section: Introductionsupporting
confidence: 66%
“…Now with reference to boiler schematic diagram shown in Fig.1 E in = m 9 h 9 + m 11 h 11 (10) And total energy of outgoing mixture, E out = m g h g (11) Where m g and h g are the mass flow rate and specific enthalpy of hot combustion product i.e. flue gas respectively.…”
Section: B Exergy Analysismentioning
confidence: 99%
“…In addition, excess air also affects the quality of combustion [13]. Arefdehgani, 2015, stated that by reducing excess air in combustion, increasing the temperature of combustion products, and decreasing the value of excess air from 0.4 to 0.15, the energy and exergy efficiencies increase 0.497% and 0.46%, respectively [18]. Rosen & Tang, 2008, reported that Energy and exergy efficiency increases by 3.5% when the stack-gas temperature decreases from 149°C to 87°C [19].…”
Section: Resultsmentioning
confidence: 99%